Exploration of Nekton and Environmental Damage Impact at the Gajah - Hasbiyan Rosyadi; Lia Kusumaningrum; Alief Himmatu Nisa; Avandi Latrianto; Nabilah Farahdilla; Raisa Noor Safira; Arif Nur Rifki; Adies Mauridzka Natasya (Jurnal Ilmu Ilmu Kehutanan, 2024)
The Gajah Mungkur Reservoir (WGM) is located south of the center of Wonogiri Regency, Central Java. The variety of aquatic biotas, such as fish, in WGM is quite diverse due to the many rivers flowing into it. This identification is important because regions in Indonesia have a diversity of different types of fish and endemic types. The data collection locations were divided into four stations in the WGM. The diversity of nekton was studied using two methods, namely active and passive methods, and data were also collected on abiotic parameters, including TDS, water temperature, brightness, DO, and pH. The nekton found in this study consisted of 11 families comprising 15 species of fish and two species of shrimp. The dominant family was the Cyprinidae family, with six species: Hampala macrolepidota, Dangila cuvieri, Osteochilus vittatus, Barbonymus gonionotus, Rasbora argyrotaenia, and Oxyeleotris marmorata. The TDS levels ranged from 790-1050, water temperature from 28.9-30.4°C, brightness from 42-83 cm, DO from 3.55 to 4.8 ppm, and pH from 8.5-8.9. The Shannon-Wiener diversity index showed a value of 1.07-1.89, the evenness index ranged from 0.65 to 0.97, and the species richness index was within the 0.54-2.37 range. This sedimentation results in soil formation that local residents use for agriculture, especially in planting palawija crops. Sedimentation can also reduce the fishery areas within the reservoir and cause habitat displacement for nekton. Additionally, Mimosa pigra plants have been found to inhabit the sedimented soil, which may affect the water quality and ecosystem of the reservoir